Accelerate : building strategic agility for a faster moving world - Kotter, John P. (Harvard : Harvard Business School, 2014)
The author explains how traditional organizational hierarchies evolved to meet the daily demands of running an enterprise. He also advocates a new system - a second, more agile, network-like structure that operates in concert with the hierarchy to create what he calls a "dual operating system".
osa 08/01/2019, ijb, 28/01/2019
Loans
Keywords: Organizational change; Strategic planning; Management